Medical Informatics Europe 1991 Proceedings, Vienna, Austria, August 19–22, 1991 - Adlassnig, Klaus-Peter; Grabner, Georg; Bengtsson, Stellan; Hansen, Rolf (Springer Berlin Heidelberg, 1991)
This volume contains the proceedings of the Tenth International Congress on Medical Informatics, MIE 91, that will be held in Vienna, Austria, August 19-22, 1991. The MIE 91 Congress was organized by the European Federation for Medical Informatics (EFMI) in cooperation with the Austrian Computer Society (OCG) and the Austrian Society for Biomedi cal Engineering (OGBMT). It follows the previous congresses in Cambridge (1978), Berlin (1979), Toulouse (1981), Dublin (1982), Brussels (1984), Helsinki (1985), Rome (1987), Oslo (1988), and the Congress 1990 in Glasgow. The proceedings contain 199 contributions to the MIE 91 Congress. They cover all presentations which are part of the scientific programme of MIE 91, among them 157 paper presentations with an average of five pages, 28 poster presentations again with an average of five pages, and 14 abstracts of demonstrations with an average of one page. The papers included were selected by an International Programme Committee out of over 300 submissions after careful review by at least two international reviewers (for whose estimable efforts we are especially thankful). The recommendations of the re viewers were incorporated in the final texts. Some papers were reworked by a professional translator to obtain a high quality of presentation. Several submissions could not be considered for presenta tion at MIE 91 because of shortage of congress time and limitations in the number of pages of the proceedings
Keywords: Statistics for Life Sciences, Medicine, Health Sciences; Statistics; Medizinische Informatik; Europa; Konferenzschrift -- 1991 -- Wien